A dissolução judicial das sociedades anônimas heterotípicas - Bargiona, Pedro Eugenio Pereira (2018)
The research object of this dissertation is the partial dissolution of heterotypical corporations, in which the expected characteristics of corporations, such as stability do not really occur. The goal of the research is to identify the way in which the partial dissolution of a heterotypical corporation should be processed in the current civil procedural law, including its objective identification. To do so, the first focus of the study to the company types and their expected characteristics, developing an objective test to identify situations of heterotypical forms in any kind of company. Then, in the second chapter, it proceeds to the study the case law that lead to the development of the institute of partial dissolution of societies and their theoretical bases in Brazil. In the third chapter, an analysis is made of the current hypotheses in which the exercise of the right of withdrawal is admitted, studying the grounds employed by the Superior Courts to recognize the heterotypical nature and allow the recess of the company by the rupture of the affectio societatis personalistic bound, and even the exclusion of shareholders for serious misconduct. Subsequently, in the fourth and last chapter, the Civil Procedure Code of 2015 is studied, as for the first time a rite for the partial dissolution of companies is established, including an attempt to expand its incidence for heterotypical corporations. This chapter tries to provide a proper interpretation for the technical vocabulary misused at the law. Also in this last chapter, the procedure for the seizure of company shares and the total dissolution of the company are analyzed. The conclusions of the study are the possibility of using an objective test that accurately identifies situations of heterotypical companies; the need for the authorization of partial dissolution as a form of harmonization for the constitutional principles of freedom of association and the preservation of the company with the rules that objectively apply to each case of dissolution; and the unrestricted applicability of the provisions of the Civil Procedure Code of 2015 to heterotypical corporations, but the necessary harmonization of the content of §2 of art. 599 from the Civil Procedure Code of 2015 with the interpretations given by the superior courts in the first case law that authorized the partial dissolution, recognizing the heterotypical characteristics and not of the inability to fulfill the corporate end, reason to limit the dissolution to the retiring partner